The Juntos Pilot Study: A Diabetes Management Intervention for Latino Caregiving Dyads. Issue 5 (October 2019) - Mendez-Luck, Carolyn A.; Miranda, Jeanne; Mangione, Carol M.; Yoon, Jangho; VanGarde, Aurora
Purpose: The purpose of this study was to design a culturally sensitive dyad-level diabetes intervention to improve glycemic control for older Latino adults with type 2 diabetes. Methods: This study used a pretest-posttest noncontrol group design. The intervention was developed from formative research with Mexican-origin caregiving dyads. The curriculum was adapted from 2 randomized trials of community interventions specifically designed for Latino older adults with type 2 diabetes. The curriculum consisted of communication skill-building exercises and dyad decision making on lifestyle changes to improve the older adult's blood glucose levels. Thirty-two community-dwelling dyads completed a 6-week program of one-on-one sessions with a trained program facilitator. Main outcomes were feasibility and acceptability of the Juntos program. The authors assessed feasibility by examining participant burden and retention and acceptability by participant exit interviews. Although underpowered for outcomes, A1C, health status, and dyadic communication were also assessed to evaluate whether trends suggested the effectiveness of the intervention. Results: Most participants viewed Juntos as an acceptable program and wanted the program expanded in terms of length and scope. All outcomes showed improvement from baseline through 6 months postintervention. Conclusions: Results show that Juntos is acceptable to Mexican-origin caregiving dyads and is a promising approach for effectively controlling type 2 diabetes among older Latino adults who have a family caregiver.